Orebody characterisation and structural features that govern copper and cobalt mineralisation in the eastern limb of the Lufilian Arc, Democratic Republic of Congo - Johnson, Russell Douglas (My University, 2015)
The Central African Copperbelt is located in the Lufilian Arc which straddles the border between Zambia and the Democratic Republic of Congo (DRC). Mineralisation of the cupriferous Arc is found in basal Neoproterozoic Katangan Supergroup sedimentary rocks, which in DRC are termed the Mines Series Subgroup. The Mines Series is divided into the dolomitic and carbonaceous GRAT, DStrat RSF, RSC, SD and CMN units. The composition of the units is homogeneous across the Lubumbashi district and potentially across the Katangan basin. This study focussed on the Kinsevere and Ruashi deposits in the Lubumbashi district, which are approximately 50 km apart. The study confirmed that relative eustatic sea level changes resulted in the non-deposition of the RSF and RSC stratigraphic units at Kinsevere. Sedimentation was followed by early pervasive potassic alteration and silicification at the diagenetic stage whilst a magnesian dolomitisation event resulted in alteration of potassic feldspars and recrystallisation of carbonates. Albitisation was veincontrolled and late-stage scapolitisation altered evaporitic nodules. Finally, haematisation by late iron-rich fluids circulating through the Roan Group strata resulted in oxidation of sulphides. The structural analysis of Kinsevere Central pit indicates E-W and N-S shortening whereas the Ruashi pit 1 deposit underwent NE-SW and N-S shortening. Initial shortening, associated with Kolwezian deformation (D1), resulted in the formation of NE-thrust folds and a primary set of joints. The Kolwezian deformation event (D2), reoriented the shortening direction from E-W to N-S, creating interference folds and possibly a second set of joints. The final phase in the structural evolution of the Kinsevere and Ruashi deposits was late-stage brittle deformation (faulting). Mineralisation was a multi-stage process. Disseminated chalcopyrite and carrollite were deposited from formation waters during diagenesis in a stable basin environment. Chalcopyrite, carrollite, chalcocite and bornite are predominantly located at the base of the DStrat, whereas chalcopyrite and pyrite dominate the stratigraphically higher portions of the deposits. Hypogene vein mineralisation began at the syn- to late- orogenic stage with carrollite and chalcopyrite in beddingparallel veins. Possible changes in the compression direction created the perpendicularly oriented veins that host chalcopyrite, carrollite, bornite, covellite, digenite and chalcocite. Finally a late stage of chalcopyrite and pyrite deposition occurred in and around the evaporites, indicating a strong correlation between mineralisation, evaporites and scapolitisation. iii Near-surface supergene alteration of hypogene sulphide ores, resulted in Cu-Co carbonates and oxides, such as malachite, azurite, cobaltiferous malachite, chrysocolla, kolwezite and sphaerocobaltite being deposited in vugs and pore spaces above the meteoric water line. Faulted and brecciated zones tend to have deeper supergene alteration. Between the sulphide facies at depth and the supergene oxide facies at surface is a transition zone which marks the depth to which oxidation has penetrated. Sulphur isotope analysis from the Kinsevere and Ruashi deposits suggests a sulphur contribution from a continental Red-Bed sedimentary source and from an evaporitic source.
A dissertation submitted to the Faculty of Science, University of the Witwatersrand, Johannesburg, in fulfilment of requirements for the degree of Master of Science. August 2014.
Keywords: Mineralogy - Democratic Republic of Congo - Lufilian Arc.; Copper.; Cobalt.; Sulfur - Isotopes.